ON THE SCIENTIFIC AND CREATIVE ACTIVITIES OF SHAHRUKH MIRZO - Abdunosirova Ozodaxon Botirjon qizi (TARIXIY TADQIQOTLAR, 2026)
This article presents some reflections on the cultural, construction, and improvement projects during the reign of Shah Rukh Mirzo. His personal involvement in cultural processes and charitable activities have been also analyzed using sources and scholarly literature.